Optimization of Inorganic Waste Recycling into Plant Pots Using the 4R Approach to Support the Adiwiyata Unggulan School Program - Yuliani, Euis Nina Saparina; Hernadewita, Hernadewita; Hermiyetti, Hermiyetti; Rahmi, Syifa Ur (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Inorganic waste, particularly plastic generated from school canteens and learning activities, remains a significant environmental challenge due to its non-biodegradability, which contributes to soil, water, and air pollution. Addressing this issue, this community service program aimed to enhance students' environmental awareness and practical skills in managing plastic waste by producing ecobricks, which were repurposed as eco-friendly plant pots to improve the school's aesthetic and ecological quality. Mercu Buana University implemented the program in collaboration with the Rawakalong Village Government to support SMKN 1 Gunung Sindur in achieving Exemplary Adiwiyata School status. The initiative combined participatory training sessions, hands-on Fs, and continuous mentoring, emphasizing the application of the 4R principles in the school environment. The results indicated a marked increase in students' engagement, knowledge, and skills in waste management, along with a measurable reduction in plastic waste volume. Ecobricks were successfully integrated into school greening activities, serving as both functional plant pots and tangible educational tools that reinforced sustainable behaviors. The program also contributed to the fulfillment of Key Performance Indicators (KPI) 3 and 7 and promoted experiential, community-based learning aligned with the Merdeka Belajar–Kampus Merdeka initiative. This study demonstrates that ecobrick-based interventions can transform environmental challenges into educational opportunities, fostering sustainable practices and participatory learning among students. Moreover, the program highlights the potential to scale ecobrick initiatives across broader school and community contexts, supporting environmental stewardship and institutional commitment to sustainability. These findings provide practical and theoretical insights into integrating hands-on waste management strategies into school-based ecological education programs.